2000
DOI: 10.1093/emboj/19.7.1476
|View full text |Cite
|
Sign up to set email alerts
|

Highly purified glycosylphosphatidylinositols from Trypanosoma cruzi are potent proinflammatory agents

Abstract: Vespa et al., 1994;Biron and Gazzinelli, 1995 Aliberti et al., 1996;Fearon and Locksley, 1996; Trinchieri and Scott, 1996). In addition, the early Seder et al., 1993; Abbas et al., 1996; Fearon macrophage proinflammatory cytokines by Trypanoand Locksley, 1996). During infection with T.cruzi, the soma cruzi is considered to be important in controlling induction of parasite-specific CMI is likely to be involved the infection and the outcome of Chagas' disease. Here in at least two aspects of Chagas' disease pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
218
2
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(236 citation statements)
references
References 49 publications
14
218
2
2
Order By: Relevance
“…In Toxoplasma gondi-, Trypanosoma cruzi-and Leishmania major-infected MyD88 -/-mice, the absence of IFN-c production by primed lymphocytes upon recall with the respective antigen correlated with the failure of APC to produce IL-12 upon co-incubation with protozoan antigens [36][37][38][39]. In a recent study, IL-12 and TNF-a production by DC when co-incubated with whole S.…”
Section: Discussionmentioning
confidence: 94%
“…In Toxoplasma gondi-, Trypanosoma cruzi-and Leishmania major-infected MyD88 -/-mice, the absence of IFN-c production by primed lymphocytes upon recall with the respective antigen correlated with the failure of APC to produce IL-12 upon co-incubation with protozoan antigens [36][37][38][39]. In a recent study, IL-12 and TNF-a production by DC when co-incubated with whole S.…”
Section: Discussionmentioning
confidence: 94%
“…Similar to whole parasite, YuYu EVs were enriched with TS family of glycoproteins, mucins, and mucin-associated proteins when compared to those from Y strain. Those molecules are well-established T. cruzi virulence factors [1,5,7,8,3034]. Both strains were able to release EVs suggesting that similar mechanisms of their biogenesis may occur among different T. cruzi groups [18,35].…”
Section: Discussionmentioning
confidence: 99%
“…Those molecules are involved in attachment and invasion to the host’s cell by infective forms of the parasite [46]. Previous reports showed that some of those molecules may act as proinflammatory agents during the innate immune response [7] leading to the production of nitric oxide (NO),IL-6, IL-12, and TNF-α via TLR2 by macrophages [7,8]. Major parasite surface components, such as TS/gp85 glycoproteins, mucins, and surface proteases GP63, were found in extracellular vesicles (EVs) shed by infective trypomastigote forms of the parasite [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Lipophosphoglycan (LPG) is a TLR2 agonist capable of activating mouse macrophages and human NK cells, in a MyD88-dependent manner [4244]. Also, glycosylphosphatidylinositol, that in T. cruzi activates TLR2 and TLR4 [4547], might be a PAMP present among Leishmania extracellular products. Even proteins might have unexpected capacities to interact with TLRs, as L. infantum Sir2 was demonstrated to induce the maturation of DCs in a TLR2-dependent manner with the secretion of IL-12 and TNF-α [48].…”
Section: Discussionmentioning
confidence: 99%